Gendered Dimensions of Academic Work During Wartime: Evidence from Israeli Faculty - Davidovitch, Nitza; Wadmany, Rivka (Journal of Education Culture and Society, 2025)
Aim. This quantitative study explored gender differences in academic research and teaching activities during emergencies, focusing on professional (research and teaching) and personal (work-life balance) dimensions. Methods. The study, conducted during the Swords of Iron War in Israel, offers insights into how faculty members cope with the challenges of wartime and academia’s role in reinforcing social resilience. The sample consisted of 140 faculty members (63 males, 77 females) from Israeli universities and colleges. Results. Reliability analysis revealed acceptable to questionable internal consistency for four constructs (Cronbach’s α = .637-.741); two constructs with poor reliability were excluded from analyses. Data were analyzed using MANOVA with Mann-Whitney U confirmatory tests due to unequal group sizes. Results show significant gender effects across four reliable activity domains (Wilks’ Λ = .832, p < .001, η² = .168). Women faculty members invested significantly more time in digital learning, teaching activities, and instruction planning compared to men. Mann-Whitney U tests confirmed all parametric findings, supporting robustness despite moderate assumption violations. Conclusions. Women faculty members demonstrated higher engagement across multiple professional domains during wartime, with medium effect sizes (Cohen’s d = .49-.66) indicating practical significance. The study advances methodological rigor through comprehensive reliability testing and robust analytical approaches, while acknowledging measurement challenges in crisis-specific behavioral assessment.